PENGARUH INOVASI PRODUK, KUALITAS PRODUK, CITRA MEREK TERHADAP MINAT BELI KONSUMEN PADA DUNIA ENTREPRENEUR SEPATU LOKAL DI INDONESIA - M Adhitya Wardhana; Nur Hayati; Yunus Mustaqim (Universitas Muhammadiyah Kudus, 2024)
Nowadays, the footwear or shoe industry sector in Indonesia is experiencing an upward trend. Recently, local manufacturers have faced market competition from overseas companies. They are competing to innovate and improve product quality in order to improve their brand image and attract and grow consumer buying interest in Indonesia. This research aims to analyze whether there is an influence of innovation, product quality and brand image on consumer purchasing interest in the footwear or shoe industry. This research is a qualitative descriptive qualitative approach where the researcher reviews documents originating from data sources on the internet. The results of this research show that the main key for consumers in Indonesia when they are interested in buying a particular shoe brand is if the company can present innovation and improve the quality of each of its products. It can be concluded that innovation and product quality will have a crucial influence on consumers, so that consumers will increase their buying interest in certain shoe products, if they feel that they feel they meet their criteria, such as the innovation presented and the quality of the product.